The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.nbd.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor dephosphorylation followed by internalization is coupled to neuronal death in in vitro ischemia

Abstract: Cerebral ischemia is characterized by an early disruption of GABAergic neurotransmission contributing to an imbalance of the excitatory/inhibitory equilibrium and neuronal death, but the molecular mechanisms involved are not fully understood. Here we report a downregulation of GABA(A) receptor (GABA(A)R) expression, affecting both mRNA and protein levels of GABA(A)R subunits, in hippocampal neurons subjected to oxygen-glucose deprivation (OGD), an in vitro model of ischemia. Similar alterations in the abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 57 publications
4
72
0
Order By: Relevance
“…Brain ischemia is also characterized by a downregulation of GABAergic synaptic transmission, both at the pre-and postsynaptic levels [3,4], but the mechanisms involved are not fully understood. Recent studies showed a decrease in the interaction of GABA A receptors (GABA A R) with the scaffold protein gephyrin in cultured hippocampal neurons subjected to oxygen-glucose deprivation (OGD), an in vitro model of brain ischemia, by a mechanism dependent on protein phosphatase activity [5]. The reduced interaction of GABA A R with the submembrane gephyrin lattice after OGD [6][7][8], together with the dephosphorylation of the receptors, facilitates their internalization by a clathrin-dependent mechanism [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Brain ischemia is also characterized by a downregulation of GABAergic synaptic transmission, both at the pre-and postsynaptic levels [3,4], but the mechanisms involved are not fully understood. Recent studies showed a decrease in the interaction of GABA A receptors (GABA A R) with the scaffold protein gephyrin in cultured hippocampal neurons subjected to oxygen-glucose deprivation (OGD), an in vitro model of brain ischemia, by a mechanism dependent on protein phosphatase activity [5]. The reduced interaction of GABA A R with the submembrane gephyrin lattice after OGD [6][7][8], together with the dephosphorylation of the receptors, facilitates their internalization by a clathrin-dependent mechanism [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…The GABAAR α1 protein did not show any significant changes in expression however in the hippocampus of several animals with seizures, the GABAAR α1 protein relocated from the cell surface into the cytosol of cells in the DG. Insensitivity to phenobarbital treatment has been associated with reductions in α1, α2 and α5 expression in adult rats experiencing seizures (Mele et al 2014). In cultured neurones chronically exposed to GABA, a decreased potentiation of GABA agonist binding by barbiturates has similarly being reported (Friedman et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in oxygen-glucose deprivation (OGD) cultures have shown that decreases in GABAAR expression may be the result of receptor internalisation (Mele et al 2014). Mele et al (2014) reported internalisation of the GABAAR α1-subtype 20min after OGD and that impairment in the interaction between GABAAR and gephyrin, a scaffold protein, preceded receptor internalisation (Mele et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations